Medically Refractory Multiple Sclerosis Is Successfully Treated with Plasmapheresis in a Super Morbidly Obese Pregnant Patient - Lindsey Dalka; Antoine Harb; Kael Mikesell; Gillian Gordon Perue (Case Reports in Neurological Medicine)
Multiple sclerosis (MS) is a relapse remitting immune-mediated demyelinating neurological disorder that primarily affects women of childbearing age. In most patients, the hormonal changes during pregnancy are protective against MS relapses. When relapses do occur, treatment options are limited to use of intravenous steroids and plasmapheresis rescue therapy. We present a case of steroid refractory MS-transverse myelitis with quadriplegia in a 25-year-old pregnant super morbidly obese woman. Our clinical case is unique because the severity of her relapse early in pregnancy, which was intractable and resistant to steroids. This may have been a rebound demyelination due to the discontinuation of fingolimod; a newly recognized entity by the FDA. Our case report therefore seeks to raise awareness about a potential complication of discontinuing MS disease modifying therapies, highlighting that these rebound relapses can be steroid resistant and occur despite the usual protective hormonal influence of early pregnancy and that plasma exchange is a valid treatment option. Finally, we discuss the challenges of determining exchange volumes for plasmapheresis in the super morbid obese population to secure good maternal and fetal outcomes.